2019
DOI: 10.3390/pharmaceutics11090483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrospinning on the Viability of Ten Species of Lactic Acid Bacteria in Poly(Ethylene Oxide) Nanofibers

Abstract: Lactic acid bacteria can have beneficial health effects and be used for the treatment of various diseases. However, there remains the challenge of encapsulating probiotics into delivery systems with a high viability and encapsulation efficacy. The electrospinning of bacteria is a novel and little-studied method, and further investigation of its promising potential is needed. Here, the morphology, zeta potential, hydrophobicity, average cell mass, and growth characteristics of nine different species of Lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 47 publications
(62 reference statements)
3
47
0
Order By: Relevance
“…salivarius), together with Lactococcus lactis were compared for their incorporation into PEO nanofibers. All of these species remained viable after their incorporation, and their viability correlated with cell hydrophobicity (Zupancic et al, 2019).…”
Section: Bacteria Fungi Stem Cells and Viruses In Nanofibers Bacteriamentioning
confidence: 98%
See 2 more Smart Citations
“…salivarius), together with Lactococcus lactis were compared for their incorporation into PEO nanofibers. All of these species remained viable after their incorporation, and their viability correlated with cell hydrophobicity (Zupancic et al, 2019).…”
Section: Bacteria Fungi Stem Cells and Viruses In Nanofibers Bacteriamentioning
confidence: 98%
“…To date, several types of biological products have been included in nanofibers to improve their delivery in medical applications (Figure 1). Among the cells used, probiotic bacteria have been incorporated most often (Heunis et al, 2010;Akbar et al, 2018;Skrlec et al, 2019;Zupancic et al, 2019). Cyanobacteria and fungus are also incorporated and they have therapeutic, agricultural and environmental properties.…”
Section: Biological Products In Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested how thermal behavior of nanofibers suggested possible thermal protection of probiotics in heat-processed foods. Nagy et al [177] by investigating the suitability of electrospinning for biodrugs delivery to produce vaginal drug delivery systems, concluded how nanofibers can provide long term stability for huge amounts of living bacteria if they are kept at (or below) 7 • C. The recent work of Zupancic et al [178], who studied the incorporation of a range of safe lactic acid bacteria into poly(ethylene oxide)-based nanofibers, evidenced that all of the lactic acid bacteria were viable after incorporation into nanofibers, with 0-3 log CFU/mg loss in viability, depending on the species. Moreover, the authors reported that viability can be correlated with the hydrophobicity and to the extreme length of lactic acid bacteria, whereas a horizontal or vertical electrospinning set-up did not have any role.…”
Section: Type Activity Study Referencesmentioning
confidence: 99%
“…Viability correlated with the hydrophobicity and extreme length of lactic acid bacteria, whereas a horizontal or vertical electrospinning set-up did not have any role. Therefore, electrospinning represents a promising method for the incorporation of lactic acid bacteria into solid delivery systems, while drying the bacterial dispersion at the same time [8].…”
mentioning
confidence: 99%